Is age at menarche a good predictor of future body fat? The case of a developing country. Issue 11 (1st November 2016) - Sohn, Kitae
ABSTRACT: Age at menarche has been proposed to serve as a predictor of future body fat for the developed world. Our aim in this study is to determine whether this is also the case for a developing country—Indonesia. We analyze nationally representative data, concerning 9, 543 women aged 15–62 in 2007–2008, and find that the relationship between age at menarche and body mass index is negative and statistically significant. The size of the relationship, however, is negligible. It thus appears that age at menarche is not a good predictor of future body fat in Indonesia and possibly other developing countries.